Anti-LGI1 Antibody-Associated Encephalitis Misdiagnosed as Schizophrenia: A Case Report - Zhang, Jin-he; Fu, Bing-bing; Wang, Wei; Sun, Cong-cong; Xu, Jin-jie (Schizophrenia bulletin, 2024)
Abstract Anti-leucine-rich glioma-inactivated 1 (LGI1) antibody-associated encephalitis is a rare but clinically significant form of autoimmune encephalitis, predominantly affecting middle-aged men. Its heterogeneous clinical presentation often leads to misdiagnosis, commonly as other neurological or psychiatric disorders. This report details the case of a 46-year-old male who initially presented with depressive symptoms, personality changes, and visual hallucinations. Over time, his condition progressed to include memory impairment, disorganized behavior, and seizures. Initially misdiagnosed with schizophrenia, the correct diagnosis of LGI1 antibody-associated encephalitis was eventually established through positive serum and cerebrospinal fluid (CSF) tests for LGI1 antibodies. Neuroimaging findings revealed characteristic bilateral temporal lobe lesions. The patient demonstrated marked improvement following treatment with methylprednisolone and intravenous immunoglobulin, ultimately achieving significant recovery. This case highlights the critical importance of comprehensive antibody testing and neuroimaging in patients presenting with nonspecific psychiatric and neurological symptoms to prevent misdiagnosis and delays in appropriate treatment. The article also reviews the pathogenesis, clinical manifestations, diagnostic approaches, and therapeutic strategies for LGI1 antibody-associated encephalitis, aiming to enhance clinical awareness and optimize patient outcomes.